FORMATION OF SEQUENCES OF CEMENTED LAYERS AND HARDPANS WITHIN SULFIDE-BEARING MINE TAILINGS (MINE DISTRICT FREIBERG, GERMANY) - Graupner T.; Rammlmair D.; Meima J.A.; Kock D.; Furche M.; Fiege A.; Schippers A.; Melcher F.; Kassahun A. (My University, 2007)
The roles of mineral dissolution, precipitation, transformation and mass transport processes related to formation of characteristic cemented layer-hardpan sequences were studied in low sulfide and low carbonate Freiberg polymetallic mine tailings. Using high resolution profiling, combined geochemical, geomicrobiological and geophysical methods allowed description of the process of weathering of reactive mineral phases and the position of the oxidation front in detail, as well as revealing the mechanisms of cementation of tailings predominantly by the formation of gels/poorly crystalline phases. Autochthonous and allochthonous gels reduced the porosity of cemented layers to values ≤1%, whereas secondary crystalline phases were less efficient in filling the pore space. Electron microprobe analysis of cemented tailings showed that common jarosite-group minerals contained up to about 8 wt.% PbO and 0.2-1.9 wt.% As2O5. Iron-As-Si gels reached contents of up to ~44 wt.% As2O5 in gel-rich cemented layers. Zinc was below the detection limit in the studied secondary phases. Sequential extraction of cemented and related oxidized brown silt layers confirmed that the bulk of As was bound to amorphous/poorly crystalline hydrous oxides of Fe, whereas Pb was often bound to jarosite. Zinc was found preferentially in the water-soluble and the exchangeable fractions. In the grey silt and the sand directly underlying the oxidized layers, As, Pb and Zn occurred as sulfide minerals. The main effects of the cemented layer-hardpan sequences at the studied site are (1) a temporary natural attenuation of the toxic compounds, (2) a restriction of the downward movement of the oxidation front, and (3) a reduction of the extent of the erosion of the surface of the tailings impoundment by wind and water. The potential of a heap to form cemented layers and hardpans is greatly increased by a heterogeneous distribution of grain sizes and reactive materials in the topmost zone, as well as by the occurrence of sulfide-rich tailings on top of layers with low permeability. © 2007 Elsevier Ltd. All rights reserved.